Increasing incidence of asbestosis worldwide, 1990–2017: results from the Global Burden of Disease study 2017. Issue 9 (28th May 2020) - Yang, Meng; Wang, Dongming; Gan, Shiming; Fan, Lieyang; Cheng, Man; Yu, Linling; Wang, Bin; Li, Wei; Ma, Jixuan; Zhou, Min; Chen, Weihong
Abstract : Global incidence and temporal trends of asbestosis are rarely explored. Using the detailed information on asbestosis from the Global Burden of Disease (GBD) 2017, we described the age-standardised incidence rate (ASIR) and its average annual percentage change. A Joinpoint Regression model was applied to identify varying temporal trends over time. Although the use of asbestos has been completely banned in many countries, the ASIR of asbestosis increased globally from 1990 to 2017. Furthermore, the most pronounced increases in ASIR of asbestosis were detected in high-income North America and Australasia. These findings indicate that efforts to change the asbestos regulation policy are urgently needed.